Imaginative and cooperative ways of doing research: dispositives and dispositions with care - Prates, Maria Paula; Macedo, Valéria; Mirim, Ataíde Vilharve Gonçalves Vherá; Mirim, Araci da Silva Yva (Saúde e Sociedade, 2023)
This article is focused on methodological aspects impplied in a research on the responses of indigenous peoples to COVID-19 conducted by a network of indigenous and non-indigenous women researchers in different Brazilian states. We seek to share experiences and reflections on the limits and potentialities of a research carried out in the pandemic and with the pandemic, since the sickeness felt in the bodies and collective life of the researchers was an unavoidable agent in the methodological and analytical parcourses, in dialogue with feminist debates on the theme of care.